Revista Elle Brasil: da mídia impressa à transmidiação - Carmo, Liana Costa do (2016)
This research aims to investigate how Elle Brazil magazine resizes its enunciation mechanisms on multiple platforms throughout the assembly of their transmedia project. Founded in 1945 in France and launched in 1986 in Brazil, Elle Brazil is a women's magazine, which its main thematic fields are fashion, beauty, lifestyle and health (fitness). The publication operates nowadays on the production and distribution of content on different platforms involving both printed and digital editions, a page in the website M de Mulher, from Editora Abril, and profiles on social networks such as Facebook, Instagram, Twitter, Snapchat and Periscope. This work intends to exam how Elle Brazil magazine operates the enunciation mechanisms in each media platform of its transmedia project. It also seeks to understand how the aesthesic component acts in the resizing of such mechanisms, and how the discursive interactions occur on every platform that are part of the transmedia project and that also delimit the visibility schemes involved in the performance of readers in such medias. The research starts from the hypothesis that the multiple enunciation platforms of Elle Brazil configure a transmedia narrative. It also rises the issues that each media has a distinct enunciation process; that the discursive interactions based on transitivity relationships are what enables the construction of transmedia narratives and that, in the case of transmedia narrative elaborated by Elle Brazil, the make feel goes beyond a simple reactive adjustment. The analysis is based on the theoretical and methodological framework of the Discursive Semiotics of Algirdas Julien Greimas; the Sociosemiotics of Eric Landowski, focusing on his studies on regimes of interaction, and the Plastic Semiotics, developed by authors such as Jean-Marie Floch and Ana Claudia de Oliveira. For the understanding of the enunciation processes in different medias, the studies of Jose Luiz Fiorin are prioritized and to approach the concept of transmediation, Yvana Fechine's and Henry Jenkins's research. The delimitation of the corpus was chosen from the media coverage of Elle Brazil on the Sao Paulo Fashion Week 2016 (SPFW N41) and was organized by aspectual categories which ultimately guided the analysis of each media platform and its operations within the transmedia project. The investigation of the behaviour of each media of Elle Brazil while covering the SPFW N41 showed a greater predisposition to subjectivity within their strategies of enunciation, as well as the presence of discursive interactions based on transitivity and visibility relations anchored in a wanting to be seen